(untitled) (Minerva, 2018)
This paper starts from the assumption that the same idea can be reflected in various expressions and proverbs in Latin. The paper offers as a first step an analysis of the different representations of the Latin expression operam ludere, which means “wasting time”. After describing the quotes where this expression can be found, the paper also presents other expressions and proverbs with a similar meaning, classified in a sampling scheme based on subject categories and authors.